HUBUNGAN DUKUNGAN KELUARGA TERHADAP KEPATUHAN MENJALANI TERAPI ANTIRETROVIRAL PADA PASIEN HIV/AIDS - Nur Kumala Sinta; Erwin " "; Riri " Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract   This research is a qualitative research with phenomenological approach which aimed to explore family support in obedience of taking Antiretroviral therapy in patients with HIV / AIDS. The number of  participants in this study are six people consisting of three people living with HIV and one people from each family of people living with HIV taken by purposive sampling technique. The data were collected through semi-structures interviews that use open ended questions. The results of this study have five themes, which are: participants adherence in antiretroviral therapy, the support received by participants, the support expected by participants, barrier for give support and hope in treatment. The results of this study recommends for patients to understand about HIV / AIDS so that families understand about the transmission of HIV / AIDS, understanding good family about HIV / AIDS is one way to prevent the stigma that the patients received HIV / AIDS so that the family can provide optimal support. The most widely support that accepted by participants is emostional support in taking antiretroviral drugs so that patients adhere to treatment.   Keywords: Antiretroviral, Family Support, HIV/AIDS, Obedience